1998
DOI: 10.1590/s0066-782x1998000300005
|View full text |Cite
|
Sign up to set email alerts
|

Evolução intra-hospitalar e seguimento pós-alta de pacientes idosos atendidos com insuficiência cardíaca congestiva na unidade de emergência

Abstract: Purpose -To evaluate the in-hospital (IH) outcome and the short-term follow-up of predominantly elderly patients presenting to an emergency room (ER) with congestive heart failure (CHF). Methods -In an 11 month period, 57 patients presenting to the ER with CHF were included. Mean age was 69+15 years (27 to 94) and 39 (68,4%) A síndrome de insuficiência cardíaca congestiva (ICC) apresenta prevalência de 1 a 2% na população geral 1-3 . Em indivíduos com idades entre 65 e 67 anos, esse número eleva-se para 23% 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
3
5
1
2
Order By: Relevance
“…In relation to gender, we identified that 71% of the patients with DHF in general were male, and 78% of HF patients with chagasic etiology were male, as corroborated by other studies [11][12][13] assessing elderly patients hospitalized due to the disease in our country. Braga et al, 8 on the other hand, identified the male sex in 49% of the sample of chagasic patients and 55% in non-chagasic patients.…”
Section: Discussionsupporting
confidence: 86%
“…In relation to gender, we identified that 71% of the patients with DHF in general were male, and 78% of HF patients with chagasic etiology were male, as corroborated by other studies [11][12][13] assessing elderly patients hospitalized due to the disease in our country. Braga et al, 8 on the other hand, identified the male sex in 49% of the sample of chagasic patients and 55% in non-chagasic patients.…”
Section: Discussionsupporting
confidence: 86%
“…Ischemic etiology in a bigger proportion was also observed in HFREF cases, a result that corresponds to those found by Villacorta et al 19 .…”
Section: Discussionsupporting
confidence: 90%
“…4–19 While providing valuable information and suggesting the need for a prediction rule, these studies are limited in their clinical applicability and translation to the acute care setting. Data from inpatient sources have been combined with data from outpatient sources, 4,5,711,14,16,17,20 retrospective chart review methodology has been employed 612,14–17 , and large databases designed for other purposes have been analyzed in an attempt to understand risk for poor outcomes. 16 Moreover, the impact of decision making in the acute setting on outcomes measured at 30-days and beyond is blurred by outpatient management decisions and patient health behavior in the time between hospitalization and outcomes assessment.…”
Section: A Introductionmentioning
confidence: 99%